Online Health and Antibiotic Information-Seeking Behavior Among University Students - Adila Awaludin; Dewi Nurhidayah; Nitya Nurul Fadilah; Tania Rizki Amalia; Nadira Alvi Syahrina (Universitas Airlangga, 2026)
Background: The Internet plays an important role in providing health information, particularly among university students. However, limited guidance from healthcare professionals may contribute to misinformation and inappropriate antibiotic use in the community. Understanding online health-seeking behaviors, especially regarding antibiotics, is important for effective public health promotion strategies; however, related research remains limited. Objective: This study aimed to investigate the patterns and motivations of Internet use related to seeking health and antibiotic information, including online purchasing behavior and self-medication practices, among university students in Tasikmalaya. Methods: This cross-sectional study used stratified sampling of 132 non-health students at Universitas Perjuangan Tasikmalaya. Data were collected using a questionnaire on internet use related to health information seeking and antibiotic self-medication. Results: Most students (94.7%) used the Internet to search for health-related information, while 65.2% searched specifically for antibiotic information. More than half of the respondents (58.3%) reported self-medicating with antibiotics, and 57.6% purchased pharmaceutical products online. Female students were significantly more likely than male students to seek health information (OR= 7.0; P = 0.021), seek antibiotic information (OR= 4.0; P = 0.001), and purchase pharmaceutical products online (OR= 2.8; P = 0.013). Convenience and lower prices were the main reasons for making online purchases. Additionally, 75.3% of students reported limited time to consult healthcare professionals as a reason for self-medicating with antibiotics. Conclusion: University students frequently use the Internet to seek health- and antibiotic-related information. Strengthening digital health promotion and oversight of online pharmaceutical sales is important to support rational antibiotic use.